The Influence of HbA1c and Gestational Weight Gain on Pregnancy Outcomes in Pregnant Women With Gestational Diabetes Mellitus - Zhang, Qiuhong; Lee, Chee Shin; Zhang, Lixia; Wu, Qi; Chen, Yunyan; Chen, Danqing; Qi, Lu; Liang, Zhaoxia (Frontiers in Medicine, 2022)
Background To investigate the influence of HbA1c level and GWG on pregnancy outcomes in pregnant women with GDM. Methods A total of 2,171 pregnant women with GDM were retrospectively included and categorized as follows: (1) normal (HbA1c <6%) and elevated (HbA1c ≥6%) HbA1c groups according to the HbA1c level in the second trimester, and (2) inadequate, appropriate, and excessive GWG groups according to the IOM guidelines. Results In pregnant women with GDM, advanced age and high pre-pregnancy BMI were high-risk factors for elevated HbA1c. Pregnant women with elevated HbA1c had higher OGTT levels than those with normal HbA1c, and the risks of adverse pregnancy outcomes were higher (P < 0.05). The risks of primary cesarean section, hypertensive disorders during pregnancy, and macrosomia in pregnant women with excessive GWG were significantly higher than those with inadequate and appropriate GWG (P < 0.05). When GWG was appropriate, the risk of hypertensive disorders during pregnancy in the elevated HbA1c group was higher than that in the normal HbA1c group. When GWG was excessive, the risks of postpartum hemorrhage, macrosomia, and neonatal asphyxia in the elevated HbA1c group were significantly higher than in the normal HbA1c group (P < 0.05). Conclusion Monitoring and controlling blood glucose levels have shown effectiveness in reducing the adverse pregnancy outcomes in women with GDM, particularly for those who had excessive GWG.